Whole child, whole family, whole community: developing shared problems of practice with Latine families related to STEM learning in early childhood - Pattison, Scott; Ramos Montañez, Smirla; López Burgos, Viviana; Tominey, Shauna; Quijano, María; Svarovsky, Gina (Frontiers in Education, 2025)
Although scholars emphasize the need to gather broad perspectives on the problems of practice guiding educational research and approaches, family voices are rarely included in these discussions. This study explored the potential for identifying shared problems of practice with families through a 2-year discussion group series with Latine parents of preschoolers. The group was part of a project exploring how informal engineering learning experiences can build on Latine family assets and support executive function skills for young children. Through discussions with participating families, several themes emerged that reflect a holistic, family-centered view on children's learning and point to potential problems of practice aligned with family goals and values: (a) supporting collaboration and relationships within families, (b) supporting children as problems solvers, (c) supporting parents as learners, and (d) creating a community of support. These themes serve to both broaden how we think about learning and development in early childhood and push on the ways that problems of practice have traditionally been conceptualized.